Classes Supported by Digital Technologies: Application of the Blog as a Virtual Tool in Biology Teaching - Tihomir Lazarević; Vera Županec; Tijana Pribićević (Inovacije u Nastavi, 2022)
Innovations in technology are rapid and workers’ roles in the virtual environment have changed. Due to the great need to educate professionals who need to adapt quickly, the modernization of teaching is gaining momentum. Blog is one of the internet tools that can be effectively implemented in education. The aim of the research is to experimentally test the effects of the application of the blog Biosoikoslogos in biology teaching in relation to traditional teaching and to evaluate the attitudes of first-grade high school students (15-16 years of age) towards the characteristics of the blog. The theoretical method, descriptive method, experimental method with parallel groups, and methods with pedagogical statistics were applied in the research. The results of the study showed that the students who used the blog achieved statistically significantly better results than the students who did not use the blog. The results also showed that the most important features of the blog are those that are the most helpful for students to directly facilitate learning. The analysis of the results shows that blog-based biology teaching is significantly more effective than traditional teaching, should be applied more frequently in practice, and students should evaluate blog features differently.